AUDIT KEUANGAN DAERAH (MENYIKAPI PERSPEKTIF PENERAPAN AKUNTANSI AKRUAL) - Miftahul Jannah; Zulkarnaini Zulkarnaini; Mariana Mariana (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of public sector auditing in supporting the implementation of accrual-based accounting systems in Indonesian local governments. The adoption of accrual accounting as part of the implementation of International Public Sector Accounting Standards (IPSAS) requires stronger oversight, transparency, and public financial accountability. This research employs a descriptive qualitative approach using observation and document analysis as data collection techniques. The findings indicate that accrual-based accounting provides more comprehensive and relevant financial information, thereby enhancing the audit function in assessing compliance, performance, and the management of assets and liabilities. However, the implementation of accrual accounting still faces challenges related to human resource limitations, technical complexity, and the need to strengthen auditor independence. This study concludes that strong synergy between accrual-based accounting systems and high-quality auditing is essential to achieving transparent, accountable, and sustainable local government financial governance.